Effect of Calcium Channel Blockers on Lower Urinary Tract Symptoms: A Systematic Review - Salman, Muhammad; Khan, Amer Hayat; Syed Sulaiman, Syed Azhar; Habib Khan, Junaid; Hussain, Khalid; Shehzadi, Naureen (Hindawi Publishing Corporation, 2017)
Background. Numerous medications are known to be associated with the development of lower urinary tract symptoms (LUTS). One such medication group is calcium channel blockers (CCB). Objective. To critically examine the literature regarding the involvement of CCB in manifestation of LUTS in humans. Methods. A systematic literature search was conducted on PubMed, SciELO, Scopus, and OpenGrey databases to find all potentially relevant research studies before August 2016. Results. Five studies met the inclusion criteria and were included in this review. Three out of five studies stated that CCB were involved in either precipitation or exacerbation of LUTS. As for the remaining two studies, one study found out that only the monotherapy of CCB was associated with increased prevalence of nocturia and voiding symptoms in young females, whereas the other study reported an inverse association of CCB with LUTS. The methodological quality of studies was considered high for four studies and low for one study. Conclusion. Healthcare providers should make efforts for an earlier identification of the individuals at risk of LUTS prior to the commencement of CCB therapy. Moreover, patients should be counselled to notify their healthcare provider if they notice urinary symptoms after the initiation of CCB.